INTERNET ADVERTISING AS A TOOL FOR DIGITAL MARKETING OF THE ENTERPRISE - ARKHYPOVA, Tetiana; AVRAMENKO, Nataliya (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article reveals the peculiarities of using Internet advertising as a tool of digital marketing of the enterprise from a practical point of view. It is defined that Internet advertising is advertising that is placed on the Internet, especially on recommended and popular websites, with the purpose of presenting products on the Internet to a wide audience. The following types of Internet advertising are characterized: social media advertising (works best for businesses that are active on social media and have a large following), paid search advertising (allows businesses to attract the attention of the audience in a more targeted way than with conventional search), native advertising (ads look like "apps" that follow the searcher’s path to discovery), display advertising (ad networks can use data and machine learning to offer businesses more effective targeting strategies and more relevant ads), contextual advertising (works on the "pay-per-click" principle), teaser ad (a standard ad consists of a title, text and image), e-mail marketing (a type of Internet advertising in which letters are sent to the postal addresses of customers), Push notifications (a small rectangular block with images and text that appears in the lower right corner of the screen), advertising in mobile applications (allows you to reach potential customers using smartphones, devices that are actively used during the day), advertising in messengers (the company can advertise its products through group chats or create a community for quick communication with customers), content marketing (involves creating relevant content for the audience that answers their specific requests), video advertising (allows you to tell stories about the company’s activities, in particular about products, emphasize its advantages and demonstrate the individuality of the brand), targeted advertising (delivers advertising messages to customers based on their specific characteristics, interests and preferences). The main trends in the development of digital advertising in Ukraine are highlighted. It was found that in addition to the main types of Internet advertising, in recent years, enterprises began to actively use other types of Internet advertising tools, such as: online games, e-mails, pop-up windows, etc. It has been established that Internet advertising should be called one of the most flexible digital marketing tools for promoting and selling products on the market. It was determined that today Internet advertising is a promising way to widely promote the activities of enterprises in the virtual space. It has been established that Internet advertising has a number of advantages, in particular, a large cycle, rapid dissemination of information, high informativeness, promptness of updating information, the possibility of feedback, unobtrusive advertising links. The purpose of Internet advertising is to use the opportunity to present to the audience such information as text, graphics, sound, video images, thereby providing as much information as possible about products.